Clinical manifestations of congenital insensitivity to pain with anhidrosis (2020)
Introduction: The congenital insensitivity to pain with anhidrosis (HSAN IV) is a rare disease, which results in different with multisystem symptoms, impacting cognitive functions that affect negatively the quality of life not only in patients but also in relatives. It is estimated that most individuals suffering from this disease die before turning three years of age due to the complications that arise from this condition. Objective: Review the clinical symptomatology of this disease and the neurocognitive alterations that occurred in 145 cases of patients with HSAN IV reported in the scientific literature between 2000 and 2017. Findings: The review allowed to identify the most frequent clinical symptoms in patients with HSAN IV: fever, anhidrosis, osteomyelitis, fractures, arthropathies and avascular necrosis. Conclusions: There is a scientific ignorance of the impact of HSAN IV on the behavior and superior functions in patients affected by this disease. © 2020, Universidad del Norte. All rights reserved.